Novel phospholipase C zeta 1 mutations associated with fertilization failures after ICSI. Issue 8 (26th July 2019) - Torra-Massana, Marc; Cornet-Bartolomé, David; Barragán, Montserrat; Durban, Mercè; Ferrer-Vaquer, Anna; Zambelli, Filippo; Rodriguez, Amelia; Oliva, Rafael; Vassena, Rita
Abstract: STUDY QUESTION: Are phospholipase C zeta 1 ( PLCZ1) mutations associated with fertilization failure (FF) after ICSI? SUMMARY ANSWER: New mutations in the PLCZ1 sequence are associated with FFs after ICSI. WHAT IS KNOWN ALREADY: FF occurs in 1–3% of ICSI cycles, mainly due to oocyte activation failure (OAF). The sperm PLCζ/PLCZ1 protein hydrolyzes phosphatidylinositol (4, 5)-bisphosphate in the oocyte, leading to intracellular calcium release and oocyte activation. To date, few PLCZ1 point mutations causing decreased protein levels or activity have been linked to FF. However, functional alterations of PLCζ/PLCZ1 in response to both described and novel mutations have not been investigated. STUDY DESIGN, SIZE, DURATION: We performed a study including 37 patients presenting total or partial FF (fertilization rate (FR), ≤25%) after ICSI occurring between 2014 and 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients were divided into two groups based on oocyte evaluation 19 h post ICSI: FF due to a defect in oocyte activation (OAF, n = 22) and FF due to other causes ('no-OAF', n = 15). Samples from 13 men with good fertilization (FR, >50%) were used as controls. PLCζ/PLCZ1 protein localization and levels in sperm were evaluated by immunofluorescence and western blot, respectively. Sanger sequencing on genomic DNA was used to identify PLCZ1 mutations in exonic regions. The effect of the mutations on protein functionality was predicted in silico using the MODICT algorithm. Functional assays were performed by cRNA injection of wild-type and mutated forms of PLCZ1 into human in vitro matured metaphase II oocytes, and fertilization outcomes (second polar body extrusion, pronucleus appearance) scored 19 h after injection. MAIN RESULTS AND THE ROLE OF CHANCE: In the OAF group, 12 (54.6%) patients carried at least one mutation in the PLCZ1 coding sequence, one patient out of 15 (6.7%) in the no-OAF group ( P < 0.05) and none of the 13 controls ( P < 0.05). A total of six different mutations were identified. Five of them were single-nucleotide missense mutations: p.I120M, located at the end of the EF-hand domain; p.R197H, p.L224P and p.H233L, located at the X catalytic domain; and p.S500 L, located at the C2 domain. The sixth mutation, a frameshift variant (p.V326K fs * 25), generates a truncated protein at the X-Y linker region. In silico analysis with MODICT predicted all the mutations except p.I120M to be potentially deleterious for PLCζ/PLCZ1 activity. After PLCZ1 cRNA injection, a significant decrease in the percentage of activated oocytes was observed for three mutations (p.R197H, p.H233L and p.V326K fs*25), indicating a deleterious effect on enzymatic activity. PLCZ1 protein localization and expression levels in sperm were similar across groups. FRs were restored (to >60%) in patients carrying PLCZ1 mutations (n = 10) after assisted oocyte activation (AOA), with seven patients achieving pregnancy and live birth. LIMITATIONS, REASONS FOR CAUTION: Caution should be exerted when comparing the cRNA injection results with fertilization outcomes after ICSI, especially in patients presenting mutations in heterozygosis. WIDER IMPLICATIONS OF THE FINDINGS: PLCZ1 mutations were found in high frequency in patients presenting OAF. Functional analysis of three mutations in human oocytes confirms alteration of PLCζ/PLCZ1 activity and their likely involvement in impaired oocyte activation. Our results suggest that PLCZ1 gene sequencing could be useful as a tool for the diagnosis and counseling of couples presenting FF after ICSI due to OAF. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by intramural funding of Clínica EUGIN, by the Secretary for Universities and Research of the Ministry of Economy and Knowledge of the Government of Catalonia (GENCAT 2015 DI 049 to M. T.-M. and GENCAT 2015 DI 048 to D. C.-B.) and by the Torres Quevedo Program from the Spanish Ministry of Economy and Competitiveness to A. F.-V. No competing interest declared.